Explaining Japan’s Revolving Door Premiership: Applying the Leadership Capital Index - Burrett, Tina (2016)
The tenure of Japanese prime ministers is famously short. Between 2006 and 2012 Japan changed prime minister once a year. What factors can explain Japan’s revolving-door premiership? To explore this puzzle, this article applies the Leadership Capital Index (LCI) developed by Bennister, ’t Hart and Worthy (2015) to case studies of the nine Japanese prime ministers holding office between 2000 and 2015. Leadership capital is the aggregate of leaders’ political resources: skills, relations and reputation. The LCI thus allows analysis of the interplay between individual capacities and contextual conditions in determining leaders’ ability to gain, maintain and deploy power. The LCI is applied to answer two questions. Firstly, what accounts for the short tenure of many Japanese premiers? In which of the LCI’s three leadership dimensions do Japanese leaders lack capital? Secondly, what forms of capital allow some prime ministers to retain office for longer than average (>2 years)? In particular, the article analyses the leadership of Junichiro Koizumi (2001–2006) Japan’s longest serving prime minister since the 1970s, and incumbent Prime Minister Shinzo Abe, who has held office for three years since December 2012. As well as utilising the LCI to comparatively analyse the tenure of Japan’s prime ministers, this article tests the applicability of the Index beyond Western parliamentary democracies.